Does Nigeria Non-Renewable Resource Abundance Leads to Macroeconomic Performance? A Trend Analysis (1970-2014) - Ajayi, Felix Odunayo; Adelowokan, A. Oluwaseyi; Ogunyomi, Oluwatosin O. (ABC Journal of Advanced Research, 2021)
Theoretically, natural resource abundance is expected to create national wealth; however, the inconclusiveness in the literature and among the African rich resources motivated this study. Our paper investigated that does Nigeria’s non-renewable resource abundance leads to sustainable macroeconomic performance? To achieve the objectives of this study, our paper employs descriptive trends analysis, using tables and charts to measure the relationship between the non-renewable resource abundance, proxied as oil and gas variables, and the selected macroeconomic variables to draw an inference within the study period of 1970 – 2014 in Nigeria. In summary, our study concludes that an inverse relationship exists between non-renewable resource abundance and macroeconomic performance in Nigeria for the covered period 1970 – 2014. Therefore, our study conforms to the existing studies of Sachs & Warner, 2001; Gylfasson, 2005, VanPloeg and Venables, 2013 that African rich-resources countries, including Nigeria, a non-renewable resource abundance retards macroeconomic performance within the period of study. Nonetheless, this study recommends that government should consistently endeavor to increase the proportion of education expenditure to total expenditure as well as same for capital expenditure to total expenditure, and finally, transform the economy from an oil-dependent economy to a non-oil driven economy, that is diversification of the economy, which would change the non-renewable resource-abundant nation from curse to blessing and thus, guarantee sustainable macroeconomic performance in Nigeria.